What does Design for Production mean? – From Design Guidelines to Self-learning Engineering Workbenches - Wartzack, Sandro; Sauer, Christopher; Küstner, Christof (Proceedings of the 11th International Workshop on Integrated Design Engineering, 2017)
Today, product developers are highly interested in designing and assembling lightweight parts, which subsequently leads to the development of new manufacturing technologies. In order to evaluate their designs, product developers depend on manufacturing knowledge. In the last decades the manufacturing knowledge has been shared as design guidelines. But, there are no guidelines for new manufacturing technologies. To face this challenge, we started with a mathematical description of the product’s properties (metamodels) by means of data mining methods. The data has been acquired by scientists for manufacturing technologies in experimental and numerical parameter studies. We utilized the metamodels in a knowledge-based design synthesis, which is based on evolutionary multi-objective optimization. Finally, we present an answer to the question of what “Design for Production” in context of new manufacturing technologies really means.
Keywords: design for X; self-learning; data mining; Pareto-optimal design